Extreme Precipitation Trends and Meteorological Causes Over the Laurentian Great Lakes - Kunkel, Kenneth E.; Yin, Xungang; Sun, Liqiang; Champion, Sarah M.; Stevens, Laura E.; Johnson, Katharine M. (Frontiers in Water, 2022)
Trends in extreme precipitation and their causes were analyzed for events within the Laurentian Great Lakes for several periods: 1908-2020, 1949-2020, 1980-2019, and 1980-2020. Upward trends in extreme precipitation were found for multiple metrics, including the number of exceedances of return period thresholds for several durations and average recurrence intervals (ARI), the number of extreme basin-average 4-day precipitation totals, and the annual maximum daily station precipitation. The causes of extreme events were classified into 5 meteorological categories: fronts of extratropical cyclones (ETC-FRT), extratropical cyclones but not proximate to the fronts (ETC-NFRT), mesoscale convective systems (MCS), tropical cyclones (TC), and air mass convection (AMC). For daily events exceeding the threshold for 5-yr ARI, ETC-FRTs account for 78% of all events, followed by ETC-NFRTs (12%), MCSs (6%), TCs (2%), and AMC (1%). Upward trends in the number of events by cause were found for all categories except AMC. An examination of basin-wide 4-day extreme events (40 largest events during 1980-2019) found that all events were caused by ETC-FRTs (85%) or ETC-NFRTs (15%).